Biomimetic Ultra‐Black Sponge Derived from Loofah and Co‐MOF for Long‐Term Solar‐Powered Vapor Generation and Desalination. Issue 5 (26th March 2021) - Wang, Hongqiang; Zhang, Chen; Zhang, Zhihua; Zhou, Bin; Shen, Jun; Du, Ai
Abstract : Designing ultra‐black materials with strong and broadband light absorption and efficient photothermal conversion properties is of great importance in many fields, including camouflage, catalysis, thermal therapy, and solar energy conversion. The West African Gaboon viper ( Bitis rhinoceros ), a master of camouflage, features black spots on its dorsal scales. The crest‐ridge structure in its black scales has been proven to be a typical antireflection structure. Herein, an artificial biomimetic ultra‐black sponge (BUBS) that imitates the crest‐ridge structure in the black scales of B. rhinoceros is successfully fabricated through growth of vertically aligned carbon nanosheet arrays derived from cobalt‐based metal–organic framework (Co‐MOF) on a loofah sponge. The vertically aligned carbon nanosheet arrays result in enhanced broadband light absorption (up to 97.08% on average) and photothermal conversion (equilibrium temperature of 80.7 °C under 1 sun illumination) of BUBS. Benefiting from its efficient light absorption and photothermal conversion, the BUBS is incorporated into solar‐powered vapor generation and desalination devices. The BUBS shows a higher water evaporation rate and efficiency of 1.93 kg m −2  h −1 and 98.5%, respectively, compared with other state‐of‐the‐art devices under 1 sun illumination. Furthermore, the BUBS also shows continuous and high water evaporation rates and excellent salt‐rejection in various brines, ensuring its potential application in solar‐powered desalination. Abstract : Ultra‐black sponge with typical antireflection structure inspired by the crest‐ridge structures in black scales of Bitis rhinoceros is fabricated and proved to have a high solar absorption, solar‐powered vapor generation rate, and solar–thermal conversion efficiency of 98.08%, 1.93 kg m −2  h −1, and 98.5%, respectively.